Study on the Sensitivity of Bare Fiber Bragg Grating for Ultrasonic Frequencies Response under Various Temperature - Mukhtar W.M.; Mukhtar W.M.; Zailani N.S.M. (Institute of Physics Publishing, 2024)
Indexed by Scopus/ERA